The study of the age of becoming edentulous in the last 20 years in Turkey - GÜNDAY, MAHİR (ELSEVIER IRELAND LTD, 2009)
The aim of this study was to determine the age of becoming edentulous and make a comparison between the patients examined in 1987 and in 2007 at the Dental School, University of Marmara in Istanbul, Turkey. A total of 680 patients (336 in 1987 and 344 in 2007) visiting the Dental School were examined. Some of the patients had just their teeth drawn, or had already became edentulous before, and were sent to the Department of Prosthodontics, for prosthodontic treatment of their edentulous mandible or maxilla. Some of the patients have few teeth and they were extracted at the Department of Oral and Maxillofacial Surgery, they became edentulous. The age of the patients that they first become edentulous and begin to use complete denture was determined. The patients grouped according to their age, sex and being completely edentulous or edentulous in one jaw. Fisher's exact test was performed during the evaluation of quantitative data. Statistical significance level was established at p < 0.05. Between 1987 and 2007, a more than 50% decrease was observed in the number of the patients who were completely edentulous or edentulous only in one jaw. This observation is one of the indications of development of patients' care and improvement in the state of mouth health in Turkey during the last 20 years. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: Edentulous subjects in older age; Mouth health in Turkey; GERIATRIC ORAL HEALTH; DENTITION; ISSUES; ADULTS; NEEDS; HOME